2004
DOI: 10.1007/s10350-004-0570-7
|View full text |Cite
|
Sign up to set email alerts
|

Female Infertility After Ileal Pouch-Anal Anastomosis for Ulcerative Colitis

Abstract: Females with ulcerative colitis who are managed nonoperatively have normal fertility, which suggests that ulcerative colitis and medical therapy do not decrease female reproductive ability. After pelvic pouch surgery for ulcerative colitis, female fertility is significantly decreased and this problem should be discussed routinely with patients considering this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(92 citation statements)
references
References 21 publications
4
82
1
5
Order By: Relevance
“…A meta-analysis evaluating IPAA in UC patients suggested that the risk of infertility increased 3-fold post-IPAA [23] . PCL [24] with IPAA has a more pronounced effect on fertility compared to the laparoscopic approach, which produces fewer adhesions [18,19,[23][24][25][26] . Studies involving laparoscopic IPAA indicate that women undergoing these procedures have significantly higher pregnancy rates as compared to open field IPAA [27] .…”
Section: Fertilitymentioning
confidence: 99%
“…A meta-analysis evaluating IPAA in UC patients suggested that the risk of infertility increased 3-fold post-IPAA [23] . PCL [24] with IPAA has a more pronounced effect on fertility compared to the laparoscopic approach, which produces fewer adhesions [18,19,[23][24][25][26] . Studies involving laparoscopic IPAA indicate that women undergoing these procedures have significantly higher pregnancy rates as compared to open field IPAA [27] .…”
Section: Fertilitymentioning
confidence: 99%
“…For women who have not had previous pelvic surgery, their fertility is similar to age-matched peers in the general population [14]. Women who have undergone pelvic surgery have increased rates of infertility, particularly those who have had proctocolectomy with ileal pouch anal anastomosis (IPAA) [14][15][16]. A recent meta-analysis by Rajaratnam et al looking at female fertility in familial adenomatous polyposis patients post-IPAA found a 3.91-fold increased risk of infertility (95% CI: 2.06-7.44) [17].…”
Section: Fertilitymentioning
confidence: 99%
“…Transition probabilities: post-surgery complications and surgery related-mortality Transition complications rates estimated from Swenson et al 115 Chronic complication rates estimated using studies by Johnson et al 135 (fertility), Kruasz andDuek 136 (male impotence) and Abdelrazeq et al 137 (chronic pouchitis). Perioperative and post-operative mortality risks were estimated using a study reported by Roberts et al…”
mentioning
confidence: 99%
“…Chronic complication rates were estimated using studies by Johnson et al 135 (fertility), Kruasz and Duek…”
mentioning
confidence: 99%